A study of multidimensional modeling approaches for data warehouse - Mat Yusof, Sharmila; Sidi, Fatimah; Ibrahim, Hamidah; Affendey, Lilly Suriani (AIP Publishing, 2016)
Data warehouse system is used to support the process of organizational decision making. Hence, the system must extract and integrate information from heterogeneous data sources in order to uncover relevant knowledge suitable for decision making process. However, the development of data warehouse is a difficult and complex process especially in its conceptual design (multidimensional modeling). Thus, there have been various approaches proposed to overcome the difficulty. This study surveys and compares the approaches of multidimensional modeling and highlights the issues, trend and solution proposed to date. The contribution is on the state of the art of the multidimensional modeling design.